Independence Number in Path Graphs - Knor, Martin; Niepel, Ľudovít (Computing and Informatics, 2012)
In the paper we present results, which allow us to compute the independence numbers of $P_2$-path graphs and $P_3$-path graphs of special graphs. As $P_2(G)$ and $P_3(G)$ are subgraphs of iterated line graphs $L^2(G)$ and $L^3(G)$, respectively, we compare our results with the independence numbers of corresponding iterated line graphs.